Analisis Hukum Islam Tentang Perjanjian Bagi Hasil Tangkapan Ikan - Satria Hilmi, Muhammad; Sudarmanto, Kukuh; Septiandani, Dian; Soegianto, Soegianto (Journal Juridisch, 2023)
The purpose of this research is to understand and analyze Islamic Law the practice of profit sharing agreement for fish catch between skipper fisherman and jurah fisherman in Wedung Village. In Wedung Village, Wedung District, Demak Regency, profit-sharing system for marine catch isnot based on the provisions of the law Number 16 of 1964 concerning Fishery Profit Sharing. In the fishery profit sharing agreement in Wedung fishing community, the average Jurah fisherman gets 25- 30%, whereas the should have received at least 40 for using a motorized boat as stated in Article 3 paragraph (1) of the Law Number 16 of 1964. This research uses empirical juridical research methods. As a result, the practice of sharing agreements for fish catch in the fishermen’s Village Of Wedung Village are still carried out by way Of Verbal agreement without any written evidence. In the implementation of profit sharing fpr catch, 25-30% is for the skipper fisherman and 70-75% is for jurah fisherman. Profis sharing agreement for fishery between skipper fishermen and jurah fishermen are not in accordance with the Islamic Law. Based on the theory of Syirkah Mudharabah, all expenses to go fishing in the sea should be borne by skipper fisherman, but in practice, in addition to the energy and mind thay they have put into, juragan fisherman must also bear the cost of fishing in the sea. Judging from the Islamic Law’s justice theory, profit sharing agreement for fish catch between skipper fishermen and jurah fishermen in Wedung Village is Very detrimental to jurah fishermen because the receive an unfair share and these are far from thr values f juctice Penelitian ini bertujuan untuk memahami dan menganalisis pandangan Hukum Islam terhadap praktik perjanjian bagi hasil tangkapan ikan yang terjadi antara nelayan juragan dengan nelayan jurah di Desa Wedung. Di Desa Wedung Kecamatan Wedung Kabupaten Demak sistem bagi hasil tangkapan laut tidak mendasarkan pada ketentuan Undang-undang Nomor 16 Tahun 1964 Tentang Bagi Hasil Perikanan. Dalam perjanjian bagi hasil perikanan di masyarakat nelayan Wedung rata-rata nelayan Jurah mendapat 25-30 %, yang seharusnya minimal mendapat 40% karena menggunakan kapal motor sebagaimana Pasal 3 ayat (1) Undang-Undang Nomor 16 Tahun 1964. Penelitian ini menggunakan metode penelitian yuridis empiris. Hasilnya, praktik perjanjian bagi hasil tangkapan ikan yang terjadi di Perkampungan Nelayan Desa Wedung masih dilakukan dengan perjanjian secara lisan tanpa ada bukti tertulis. Dalam pelaksanaan bagi hasi tangkapan ikan, 25-30% untuk nelayan juragan dan 70-75% untuk nelayan jurah. Perjanjian bagi hasil perikanan antara nelayan juragan dengan nelayan jurah belum sesuai dengan hukum Islam. Berdasarkan teori Syirkah Mudharabah seharusnya seluruh biaya melaut di tanggung nelayan juragan, namun dalam prakteknya, nelayan jurah selain mengerahkan tenaga, dan pikiran, nelayan jurah juga ikut menanggung biaya melaut. Ditinjau dari teori keadilan Hukum Islam perjanjian bagi hasil tangkapan ikan antara nelayan juragan dengan nelayan jurah di Desa Wedung sangat merugikan nelayan jurah karena mendapatkan bagian yang tidak sebagaimana mestinya dan jauh dari nilai-nilai keadilan.